International Spinal Cord Injury Pain Classification: part I: background and description - Bryce, Thomas N.; Treede, Rolf-Detlef (Spinal cord, 2011)
Study design: Discussion of issues and development of consensus. Objective: Present the background, purpose, development process, format and definitions of the International Spinal Cord Injury Pain (ISCIP) Classification. Methods: An international group of spinal cord injury (SCI) and pain experts deliberated over 2 days, and then via e-mail communication developed a consensus classification of pain after SCI. The classification was reviewed by members of several professional organizations and their feedback was incorporated. The classification then underwent validation by an international group of clinicians with minimal exposure to the classification, using case study vignettes. Based upon the results of this study, further revisions were made to the ISCIP Classification. Results: An overall structure and terminology has been developed and partially validated as a merger of and improvement on previously published SCI pain classifications, combined with basic definitions proposed by the International Association for the Study of Pain and pain characteristics described in published empiric studies of pain. The classification is designed to be comprehensive and to include pains that are directly related to the SCI pathology as well as pains that are common after SCI but are not necessarily mechanistically related to the SCI itself. Conclusions: The format and definitions presented should help experienced and non-experienced clinicians as well as clinical researchers classify pain after SCI.